HemoScreen hematology analyzer compared to Sysmex XN for complete blood count, white blood cell differential, and detection of leukocyte abnormalities - Linko-Parvinen Anna-Maria; Keränen Kristiina; Kurvinen Kaisa; Tienhaara Anri (United States, 2022)
We compared a point-of-care HemoScreen hematology analyzer to an automated Sysmex XN analyzer for complete blood count (CBC) and white blood cell (WBC) differential, and evaluated its capacity to detect leukocyte abnormalities. A total of 100 K2-EDTA whole blood samples, median age 56 years (2 months to 92 years), were compared. For CBC and WBC differential we compared 74 samples with no confirmed abnormal leukocytes. For 26 samples both analyzers gave flagging regarding leukocytes and the accuracy of the flagging was compared. Abnormal leukocytes were confirmed with manual microscopy (200 cells). HemoScreen CBC and WBC differential were highly comparable to Sysmex XN for most of the essential parameters (r = 0.909–0.975). More variation was seen for basophil and monocyte counts (r = 0.452 and 0.753, respectively). Sysmex XN gave more false WBC abnormal flagging (n = 15 altogether) compared to HemoScreen. In addition, Sysmex XN, as well as HemoScreen, gave false WBC flagging for eight samples confirmed normal. The samples verified by microscopy review to truly contain leukocyte abnormalities (n = 18) were flagged abnormal with both analyzers. The specificity for analyzer flagging was 72% and 88% for Sysmex XN and HemoScreen, respectively. HemoScreen hematology analyzer is essentially comparable to Sysmex XN for CBC and WBC differential analysis. Most importantly, HemoScreen detected all the samples confirmed to include abnormal leukocytes. HemoScreen was less prone for false WBC flagging compared to Sysmex XN, thereafter requiring less microscopy review. These abilities increase its utility in small health care units. Studies with a larger number of abnormal leukocyte samples are needed to confirm HemoScreen performance.